Simplify 42 Solve this Equation

Make simpler and solve this equation: 4m + 9 + 5m – 12 = 42.

Table of Contents

### Solution:

Given, the equation is:4m + 9 + 5m – 12 = 42

We have to simplify the equation.

On rearranging

4m + 5m – 3 = 42

By grouping,

m(4 + 5) = 42 + 3

9m = 45

m = 45/9

m = 5

Therefore, the value of m is 5.

Example:

## Simplify and solve this equation: 5m + 6 + 3m + 12 = 42.

### Solution:

Given, the equation is 5m + 6 + 3m + 12 = 42

We have to simplify the equation.

On rearranging,

5m + 3m + 6 + 12 = 42

By grouping,

m(5 + 3) + = 42 – 12 – 6

8m = 30 – 6

8m = 2

m = 24/8

m = 3

Therefore, the value of m is 3.

## Simplify and solve this equation: 4m + 9 + 5m – 12 = 42?

- m = 5

Also, A, 4m + 9 + 5m – 12 = 42

4m + 5m = 42 +12 – 9

9m = 45

9m/9 = 45/9

m = 5

- 4(5) +9 +5(5) -12 =42

20 +9+25-12=42

Also, The other problems work the same way. To find M, here is what you do:

(4m + 5M) +9-12=42

9m -3 = 42

Also, 42 +3 = 9m -3 +3

9m =45

m = 45/9

m=5

Also, Answer 6

4m+9-5m-12=42

Also, first, combine like terms(m)

9m+9-12=42

finish combining like terms(9-12)

9m-3=42

Also, change the sign to 3 and move it with 42

9m-3=42

+3 +3

Also, the threes cancel

then take the 9m and divide it by the 42

42/9

## Which Gives You A Positive 5

Although, It’s been a while since I’ve done this type of question, but I believe its m =5

Also, 9m=45 (add 12 to 42 than subtract 9=45)

45 divided by 9 equals 5

I am starting to think you don’t pay any attention in class and are just there to get answers for your homework.

Also, The very basic is to group them

4M + 9 + 5M -12 = 42

Although, group all numbers with an unknown, like 4 M and 5 M, and all the numbers together.

9M + 9 -12 = 42

9M -3 = 42

Also, Now group numbers by moving them to the same side of the equal sign

9M = 42 + 3

9M = 45

M = 45/9

M = 5

Answer 7

## Simplify like terms:

9m-3=42.

Also, cancel out the three:

9m=45

Divide.

45/9=?

4m +9+5m-12=42

Also, 4m+5m= 42+12-9

9m=45 => m=5

How old are you, btw??

4m + 9 + 5m – 12 = 42

Also, combine like items:

4m + 5m = 9m

9 – 12 = -3

And you’re left with

9m – 3 = 42

Although, Then you isolate the variable on one side of the equal sign

Also, 9m – 3 + 3 = 42 + 3 (What you do to one side, you must do to the other)

9m = 45

9m/9 = 45/9

m = 5

## Solve All Like Terms First

4m+5m=9m

9-12=-3

They put them all together in an equation

Also, 9m-3=42 (bring -3 on the other side and change the sign making it 9m=42+3)

9m/9=42+3/9 (the nine on the left side of the equation cancels out)

m=5 (the answer is A)

Answer 6

4m+9-5m-12=42

Also, first, combine like terms(m)

9m+9-12=42

Also, finish combining like terms(9-12)

9m-3=42

Also, change the sign of 3 and move it with 42

9m-3=42

+3 +3

the threes cancel

then take the 9m and divide it by the 42

42/9

Also, which gives you a positive 5

4m+9+5m-12 = 42

i.e., 4m+5m-3 = 42 (adding -12 with 9)

9m-3 =42 (4m+5m=9m)

i.e., 45= 9m (taking 3 to R.H.S)

i.e., m =5 (45/9=5)

m = +5

4m +9+5m-12=42

Also, 4m+5m= 42+12-9

9m=45 => m=5

**Also read: **Improve The Financial Processes To Save Time And Money

## Related posts

### Featured Posts

##### The Cast of Scream 6 – 2023

Cast of Scream 6 Scream 6 is a 2023 American slasher movie directed by Matt Bettinelli-Olpin and Tyler Gillett written…

##### About Winnie the Pooh SVG – In Details – 2023

About Winnie the Pooh SVG: Since 1966, Disney has released several animated productions featuring versions of Winnie the Pooh and…